2014
DOI: 10.1088/0953-8984/26/12/126001
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic transitions in cubic Mn3Ga

Abstract: The structural, magnetic and electron-transport properties of cubic Mn3Ga have been investigated. The alloys prepared by arc melting and melt-spinning show an antiferromagnetic spin order at room temperature but undergo coupled structural and magnetic phase transitions at 600 and 800 K. First-principles calculations show that the observed magnetic properties are consistent with that of a cubic Mn3Ga crystallizing in the disordered Cu3Au-type structure. The samples exhibit metallic electron transport with a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 27 publications
6
35
0
Order By: Relevance
“…Therefore, the Curie temperature of D0 22 -Mn 3 Ga cannot be determined because of the occurrence of structure transition at temperature below the magnetic phase transition. The observed structure transition is in agreement with recent studies which were confirmed in temperature-dependent XRD studies, differential scanning calorimetry and temperature dependence of magnetization [7], [15], [16]. Nevertheless, both samples with high transition temperature are very suitable for application at and above room temperature.…”
Section: B Magnetic Propertiessupporting
confidence: 91%
“…Therefore, the Curie temperature of D0 22 -Mn 3 Ga cannot be determined because of the occurrence of structure transition at temperature below the magnetic phase transition. The observed structure transition is in agreement with recent studies which were confirmed in temperature-dependent XRD studies, differential scanning calorimetry and temperature dependence of magnetization [7], [15], [16]. Nevertheless, both samples with high transition temperature are very suitable for application at and above room temperature.…”
Section: B Magnetic Propertiessupporting
confidence: 91%
“…16. This type of low-temperature resistivity behavior has been observed in other Mn-based magnetic alloys such as disordered cubic Mn 3 Ga. 11 Both samples show positive and small magnetoresistance (0.7% at room temperature). This may be attributed to the spin disorder due to competing ferro-and antiferromagnetic interactions present in the films.…”
Section: -supporting
confidence: 63%
“…4(c). 11,16 The values of the residual resistivity ratio (RRR) defined as q 305 K /q 2 K for the Mn 2 Ga 5 and Mn 3 Ga films are close to one, indicating that the films have substantial structural disorder which would produce spin disorder because of likely antiferromagnetic Mn-Mn interactions. If the low-temperature spin structure has spin-glass-like feature, the conduction electrons may exhibit scattering from a nearly degenerate two-level system as suggested in Ref.…”
Section: -mentioning
confidence: 91%
See 1 more Smart Citation
“…It has been reported to have tetragonal, hexagonal and face-centered cubic crystal structures when subjected to different heat treatments 24 . Hexagonal Mn 3 Ga (70–74 at.% Mn) has a D0 19 -type structure with space group P63/mmc 5 , as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%